The Double Writing of Agota Kristof and the New Europe - Martha Kuhlman (Studies in 20th & 21st Century Literature, 2003)
Agota Kristof, a native of Hungary who lives in Switzerland and writes in French, has written a trilogy of novels that explore the borderlines and fractured history of the "New Europe": The Notebook (1986), The Proof (1988), and The Third Lie (1991). Set in an unnamed Central European country, the novels traverse the three successive shocks of Nazism, Socialism, and Capitalism. Through the device of identical twin narrators, brothers Lucas and Claus, Kristof inscribes the story/history (histoire) with a "double writing" that opposes personal and official histories. But this opposition is not a simple one, for the two versions are combined into a narrative Moebius strip that continually exposes the act of its own composition. Although her writing is deceptively naive, the narrative structure of the trilogy forms the architecture of a fictional labyrinth that can be read as a parable for Europe. Which narrative is the authoritative one? Each successive novel rewrites the story of the previous one in a self-consuming fictional trap, a reminder that history is always narrated by the victor. This article demonstrates how Kristof's works enact, both in the narrative and at the linguistic level, the "double writing" of history, and relates her works to contemporary debates that trouble the conscience of the New Europe.
Keywords: Agota Kristof; New Europe; borderlines; The Notebook; The Proof; The Third Lie; Central European country; Central Europe; Nazism; Socialism; Capitalism; identical twin narrators; identical twin; Lucas; Claus; histoire; story; history; double writing; personal histories; official histories; narrative Moebius; composition; naive; trilogy; parable for Europe; parable of Europe; self-consuming; victor; history narrated by the victor; conscience of the New Europe